2014
DOI: 10.1016/j.apmr.2014.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Brief Fatigue Inventory in Community-Dwelling Older Adults

Abstract: Objective To investigate the psychometric properties of the Brief Fatigue Inventory (BFI) in community-dwelling older adults. Design Cross-sectional validation study. Setting Community-based longitudinal cohort aging study in Westchester County, New York. Participants Subjects (N=302) were non-demented older adults (mean age 76.44 years, 54% female). Interventions Not applicable. Main Outcome Measures BFI total, severity, and interference summation scores. Results A Principle Component Analysis (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…The single domain demonstrated in the factor analysis and concordance with injury severity and recovery measures confirmed the validity of the scale for burn patients. These attributes are similar to that demonstrated in the use of the BFI in other populations [7,29,30]. The significant correlation of BFI with BSHS-B scores in the multivariate model established criterion validity.…”
Section: Discussionsupporting
confidence: 68%
“…The single domain demonstrated in the factor analysis and concordance with injury severity and recovery measures confirmed the validity of the scale for burn patients. These attributes are similar to that demonstrated in the use of the BFI in other populations [7,29,30]. The significant correlation of BFI with BSHS-B scores in the multivariate model established criterion validity.…”
Section: Discussionsupporting
confidence: 68%
“…There were strong positive relationships between subscales of the STI-CF (particularly for mental effort and motivation) with error, ratio, and subtraction scores on the TMT, which are thought to be more sensitive to aspects of executive functioning that require maximizing attentional demands and rearranging resources, supporting the limited capacity framework for cognitive fatigue. Coupled with a lack of a relationship with neuropsychological measures that are not related to this construct, this provides further evidence that fatigue and executive control may be related (29, 56, 72) and that the STI-CF may be a useful measure for examining this relationship.…”
Section: Discussionmentioning
confidence: 88%
“…A recent study validating the scale in older adults found that it had a bi-dimensional factor structure (fatigue severity and fatigue interference) with good reliability (56). The STI-CF was hypothesized to have a positive but weak relationship with the BFI since the scales measure different aspects of fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…Fatigue severity was measured using the Brief Fatigue Inventory (BFI) severity subscale [26]. This subscale was chosen as it represents a dimension of fatigue which is more highly associated with performance of physical tasks by older adults compared to fatigue interference which is also measured by the BFI [39]. The severity subscale is an average of 3 items from the BFI in which fatigue severity in different contexts is measured on a 0 – 10 scale.…”
Section: Methodsmentioning
confidence: 99%